Revision der Oxypoda-Untergattung Cyrtonychochaeta Scheerpeltz, 1947, stat. n., und alpiner Arten der Untergattung Podoxya Mulsant & Rey, 1875 (Coleoptera, Staphylinidae, Aleocharinae). - Zerche, Lothar (Contributions to Entomology = Beiträge zur Entomologie, 1995)
A revision of the Oxypoda subgenus Cyrtonychochaeta Scheerpeltz, 1947, stat. n., and of alpine species of the subgenus Podoxya Mulsant & Rey, 1875 (Coleoptera, Staphylinidae, Aleocharinae). Cyrtonychochaeta Scheerpeltz, 1947 is recognized as a subgenus of Oxypoda Mannerheim, 1831 (comb. et stat. n.). Only two of the eight species of Cyrtonychochaeta - seven of them originally described as Cyrtonychochaeta and one transferred to the genus - remain valid: Oxypoda (Cyrtonychochaeta) hoelzeli Scheerpeltz, 1947 comb. n. (type species) and Oxypoda (Cyrtonychochaeta) nimbicola Fauvel, 1900. - The following new synonymies are established: Cyrtonychochaeta fugaevaccarum Lohse, 1968 syn. n. = Oxypoda (Cyrtonychochaeta) hoelzeli Scheerpeltz, 1947; Cyrtonychochaeta falsa Lohse, 1968 syn. n. = Oxypoda (Cyrtonychochaeta) nimbicola Fauvel, 1900; Cyrtonychochaeta breiti Scheerpeltz, 1957 syn. n. = Oxypoda (Podoxya) tirolensis Gredler, 1863. - Two of the four nominal species of the Oxypoda (Podoxya) tirolensis-group remain valid: Oxypoda tirolensis Gredler, 1863, and Oxypoda densa (Fauvel, 1900). The following new synonymies are established: Oxypoda (Podoxya) glacialis Scheerpeltz, 1956 syn. n. = Oxypoda (Podoxya) densa (Fauvel, 1900); Oxypoda comellinii Lohse, 1970 syn. n. = Oxypoda (Podoxya) densa (Fauvel, 1900). - For a complete list of synonyms see p. 309: 2. Synonymie der revidierten Taxa. - Lectotypes are designated for the following species: Oxypoda tirolensis Gredler, 1863, Oxypoda confusa Ganglbauer, 1895 and Hygropora densa Fauvel, 1900. Based on constitutive characters the subgenus Cyrtonychochaeta and the Oxypoda tirolensis-group are recognized as monophyla. Their respective sister groups remain unknown. - Diagnostic keys allowing identification of the species are provided. The two species of the subgenus Cyrtonychochaeta are illustrated in detail; drawings of the genitalia are presented for the two species of the Oxypoda tirolensis-group. All the revised records are listed, and the distribution of each species is mapped. Oxypoda densa is new to the Central European fauna. Nomenclatural Actsbreiti Scheerpeltz, 1957 (Cyrtonychochaeta), syn. n. of Oxypoda tirolensis Gredler, 1863falsa Lohse, 1968 (Cyrtonychochaeta), syn. n. of Oxypoda (Cyrtonychochaeta) nimbicola Fauvel, 1900fugaevaccarum Lohse, 1968 (Cyrtonychochaeta), syn. n. of Oxypoda (Cyrtonychochaeta) hoelzeli (Scheerpeltz, 1947)peezi Scheerpeltz, 1957 (Cyrtonychochaeta), syn. n. of Oxypoda tirolensis Gredler, 1863comellinii Lohse, 1970 (Oxypoda), syn. n. of Oxypoda densa (Fauvel, 1900)confusa Ganglbauer, 1895 (Oxypoda), Lectotype now a synonym of Oxypoda tirolensis Gredler, 1863densa (Fauvel, 1900) (Oxypoda), Lectotype described as Hygropora densaglacialis Scheerpeltz, 1956 (Oxypoda), syn. n. of Oxypoda densa (Fauvel, 1900)tirolensis Gredler, 1863 (Oxypoda), Lectotypehoelzeli (Scheerpeltz, 1947) (Oxypoda (Cyrtonychochaeta)), comb. n. hitherto Cyrtonychochaeta hoelzeli